2020
DOI: 10.3390/cancers12102980
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Pattern of Endoplasmic Reticulum Protein Processing and Extracellular Matrix Proteins in Functioning and Silent Corticotroph Pituitary Adenomas

Abstract: Functioning (FCA) and silent corticotroph (SCA) pituitary adenomas act differently from a clinical perspective, despite both subtypes showing positive TBX19 (TPIT) and/or adrenocorticotropic hormone (ACTH) staining by immunohistochemistry. They are challenging to treat, the former due to functional ACTH production and consequently hypercortisolemia, and the latter due to invasive and recurrent behavior. Moreover, the molecular mechanisms behind their distinct behavior are not clear. We investigated global tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
(85 reference statements)
1
8
0
Order By: Relevance
“…In line with our reports, the high-throughput sequencing and bioinformatics analyses of several tumors have revealed that CAMs are frequently identified as hub genes based on a PPIN analysis [62][63][64]. These recent studies underline the particular importance of CAMs in tumor development and progression.…”
Section: Discussionsupporting
confidence: 87%
“…In line with our reports, the high-throughput sequencing and bioinformatics analyses of several tumors have revealed that CAMs are frequently identified as hub genes based on a PPIN analysis [62][63][64]. These recent studies underline the particular importance of CAMs in tumor development and progression.…”
Section: Discussionsupporting
confidence: 87%
“…These results suggest a reason for the lack of active ACTH secretion from these tumors. Moreover, the extracellular matrix (ECM) protein cluster is downregulated in SCAs compared to functioning ACTHomas, suggesting that this is associated with their invasive behavior (84). TREATMENT Surgery is the first-line treatment to control tumor volume for refractory corticotroph tumors, even though the postoperative recurrence rate remains high (8,85).…”
Section: Silent Corticotroph Adenomasmentioning
confidence: 99%
“…These results suggest a reason for the lack of active ACTH secretion from these tumors. Moreover, the extracellular matrix (ECM) protein cluster is downregulated in SCAs compared to functioning ACTHomas, suggesting that this is associated with their invasive behavior ( 84 ).…”
Section: Molecular Pathologymentioning
confidence: 99%
“…Mouse models of SCAs and in vitro studies showed a reduced expression of tumor suppressor genes RB1 and KLK10 , and altered expression of other genes related to tumor progression and metastasis [ 68 ]. Moreover, transcriptome and proteome analysis comparing gene expression between SCAs and functioning corticotrope adenomas identified alterations in endoplasmic reticulum protein processing and in ACTH synthesis such as the overexpression of PCSK1N, an indirect inhibitor of ACTH maturation [ 69 ]. These differences may explain the altered ACTH secretion in SCAs [ 68 , 69 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%